2010
DOI: 10.1182/blood.v116.21.3060.3060
|View full text |Cite
|
Sign up to set email alerts
|

BT062, An Antibody-Drug Conjugate Directed Against CD138, Shows Clinical Activity In a Phase I Study In Patients with Relapsed or Relapsed/Refractory Multiple Myeloma

Abstract: 3060 Background: CD138 represents one of the most reliable target antigens for identification of multiple myeloma (MM) cells and has been reported to be a highly sensitive and specific diagnostic marker of MM. BT062 (Biotest AG Dreieich, Germany) is an antibody-drug conjugate, comprised of the anti-CD138 chimerized MAb (nBT062) and the cytotoxic agent DM4. Once bound to CD138 on a target cell, the conjugate is internalized and releases DM4, leading to targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Once bound to SDC1 on the cell, the conjugate is internalized and releases DM4, which consequently leads to cell death. A study was conducted to evaluate the effect of BT062 on multiple myeloma patients heavily pretreated with revelimid, thalidomide, velcade, or carlfilzomid [ 141 , 142 ]. BT062 was well-tolerated in patients and 4% achieved partial response, 8% had a minor response, while 38% showed stable disease [ 141 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once bound to SDC1 on the cell, the conjugate is internalized and releases DM4, which consequently leads to cell death. A study was conducted to evaluate the effect of BT062 on multiple myeloma patients heavily pretreated with revelimid, thalidomide, velcade, or carlfilzomid [ 141 , 142 ]. BT062 was well-tolerated in patients and 4% achieved partial response, 8% had a minor response, while 38% showed stable disease [ 141 ].…”
Section: Introductionmentioning
confidence: 99%
“…Successful applications of radioimmunotherapy drugs, such as iodine-131-labeled anti-CD138 mAb, in clinical trials have indicated to some extent that CD138 is a high-potential target, especially in the treatment of refractory and relapsed MM [37]. A phase II clinical trial by Jagannath et al using BT062, an antibody-drug conjugate directed against CD138, also indicated the potential of CD138 as a target in MM treatment [38].…”
Section: Discussionmentioning
confidence: 99%